EXPERIMENTAL BACKGROUND OF THERMOMETRY USING WITH DIAGNOSTIC PURPOSES IN SOFT TISSUE GUNSHOT DAMAGES - Khomenko, I.P.; Tertyshnyi, S.V.; Vastyanov, R.S.; Talalayev, K.O.; Turchin, M.I.; Panasenko, S.I. (World of Medicine and Biology, 2022)
The problem of treatment of gunshot wounds remains to be one of the most pressing and unresolved issues of modern surgery. Gunshot wounds diagnosis is currently ineffective. There is a need to improve the content and scope of medical care with the possible diagnosis chain strengthening. A promising direction in gunshot wounds diagnosis and surgical treatment is thermographic examination followed by a multimodal approach to the soft tissues gunshot defects reconstruction. Chronic experimental studies were performed using Shinshilla rabbits which were undergone gunshot wounds, followed by 5 days of laboratory, morphological and functional examinations. The results indicate the thermometry diagnostic importance in soft tissues gunshot wounds because this method allows justifying the temperature response over the anatomical area of the gunshot defect and its dependence on the severity or prevalence of the lesion. The obtained data have the perspectives of clinical application, which may be a prerequisite for diagnosis improving and detailing, septic complications early prediction and the selection of adequate therapeutic surgical tactics or prevention of this type of gunshot and explosive injuries.
Keywords: gunshot wounds; soft tissues; thermometry; perforating vessel; diagnosis; prevention